Perbedaan Perbandingan Sosial pada Remaja Pengguna Instagram dan TikTok - Saputra, Riyan Hidayat (Lembaga Yasin AlSys, 2024)
This research aims to see differences in social comparisons among teenage users of Instagram and TikTok. This research uses a quantitative approach in its methodology. Sampling in this study used a purposive sampling method. The sample in this study was 340, consisting of 170 teenage Instagram users and 170 teenage TikTok users. This research uses a scale compiled by Gibbons & Buunk, (1999), namely the Iowa-Netherlands Comparison Orientation Measure (INCOM) using the dimensions proposed by Festinger, (1954) which are found in Gina's (2019) research, namely ability and opinion. The analysis results use the Independent Sample T-test and the Mann Whitney test as alternatives, because the data distribution is not normal. The results of the research showed that there was no difference in social comparison between teenage Instagram users and teenage TikTok users.